A comparative study of 25 mcg vs 50 mcg of vaginal misoprostol for induction of labour - Aggarwal, Amika; Pahwa, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objectives of the current study were to compare the efficacy and safety of 25μg and 50μg of intravaginal misoprostol for induction of labor at term and to study the maternal and fetal outcome. Methods: A Prospective Study was done on 50 cases with 25μg misoprostol and 50 cases of 50μg of misoprostol intravaginal, repeated every 6 hourly till adequate uterine contractions or maximum 5 doses. Total dose of induction, induction delivery interval, mode of delivery, maternal and fetal outcome were recorded. Results: Mean induction delivery interval was 13.8±5.9 and 14.0±5.7 hours (P=0.9) with the 25μg and 50μg misoprostol respectively. The 25μg misoprostol group had a lower delivery rate with a single dose compared with the 50μg group (38% and 42% respectively). However, 25μg group had more deliveries than 50μg group with increasing number of misoprostol doses (36% vs. 38%, and 20% vs. 16% for 2 doses and 3 doses respectively). The need for oxytocin augmentation among participants was higher in the 25μg group (20%) than in 50 μg group (16%).This was however not statistically significant (P=0.603). At lesser initial bishop score, with 50µg misoprostol less doses are needed as compared to 25 µg and hence induction delivery interval decreases. The rates of caesarean section and operative vaginal delivery were similar in both groups. There was no significant difference in maternal side effects and neonatal outcomes among the women in the two groups. Conclusions: The 25 µg of intravaginal misoprostol administered six‑hourly appears to be as effective but safer than 50 µg for induction of labor. The use of 50 µg misoprostol may be recommended when there is a need to expedite vaginal delivery especially in cases of lesser initial bishop score.